Geopolitics at 25: An Editorial Journey through the Journal's History. Issue 5 (19th October 2020) - Agnew, John; Dalby, Simon; Flint, Colin; Mamadouh, Virginie; Newman, David; Schofield, Richard
ABSTRACT: Geopolitics is 25 years old. In this Forum former editors reflect on the journey the journal has taken in those 25 years and the wider discipline (or disciplines) in which the journal sits. Alongside a recounting of how the journal came into existence and its name change to just 'Geopolitics', the editors reflect on the resurgence and increasingly interdisciplinary nature of geopolitics as a field of study which the journal played a role in and all meticulously chronicled in its pages (or bytes); the meanings and importance of the "geo" in geo politics; the dynamics and politics of international publishing, the academic publishing industry, metrics, citation and the move online; as well as the continued Anglophone nature of political geography within a supposedly internationalising academy. This is coupled with suggestions for future avenues of research, including a plea to consider physical geography more concretely.